Pengaruh Umur Obligasi Dan Pertumbuhan Perusahaan Terhadap Peringkat Obligasi Pada Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Mursidah Mursidah; Bustam Bustam; Alimuddin Syar (Journal on Education, 2025)
This study aims to determine the effect of bond age, company growth on the rating of financial sector bonds listed on the IDX in 2020-2022 using a quantitative research approach. which aims to test theories, build facts, show relationships between variables, provide statistical descriptions, estimate and predict the results. This research will be conducted on the Indonesia Stock Exchange. This study is to test the effect of bond age and company growth variables on bond rating variables, while to analyze the effect of each variable using SPSS software. Based on the results of the study, in the financial sector, bond age has a negative effect on bond ratings listed on the IDX. This is obtained from the results of the regression analysis, namely a significance value of <0.05 (0.249> 0.05) and a calculated t value of less than 2.022 (1.172 <2.039). In the financial sector, bond age has a negative effect on bond ratings listed on the IDX, on the company growth variable (X2), a Sig value of 0.00 and a calculated t value of -13.759 are obtained. because the Sig value is less than 0.05 (0.00 > 0.05) and the calculated t value is greater than 2.022 (-13.759 < 2.022).